Influence of Some Environmental Factors on Manifestation of Familial Mediterranean Fever in Children: Clinical and Genetic Aspects - Avagyan, T.; Amaryan, G.; Budumyan, A.; Hayrapetyan, A.; Tadevosyan, A. (Caucasus Journal of Health Sciences and Public Health, 2018)
Familial Mediterranean Fever (FMF) is common in Armenia. Significant increase in number of cases has been registered in recent years, especially in children, including ones with atypical course. According to National Pediatric Center for Familial Mediterranean Fever (NPC FMF) during the last 13 years (from 2003 to 20016) annually diagnosed 300-350 new cases and has been recorded 6 fold increases of registered cases from 500 to more than 3000. According to Center of Medical Genetics and Primary Health Care (CMG) weekly visits for FMF diagnostics is exceeding 60, since 1997 to September 2016 there are registered more than 27000 FMF patients. Molecular-genetic testing is essential for diagnosis of FMF especially for cases with atypical course and coexistence with immune diseases as well.